2017
DOI: 10.15226/2374-6890/4/5/00190
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dyslipidemia and The Associated Factors Among Type 2 Diabetes Patients in Turbo Sub-County kenya

Abstract: Background: A large number of deaths worldwide are attributed to non-communicable diseases (NCDs). Diabetes, an important NCD, contributes to this large mortality mainly through cardiovascular complications. Cardiovascular disease in diabetes is caused by multiple co-morbid conditions; key of which is dyslipidemia. Objectives: This study aimed to determine prevalence of dyslipidemia and its associated factors among patients with type 2 diabetes mellitus attending Chronic Disease Management clinics (CDM) in Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 29 publications
9
22
1
2
Order By: Relevance
“…17 The current study revealed that there is a statistically significant association between dyslipidemia and physical activities. Similar findings were reported from Kenya 16 and China. 25 In this study, dyslipidemia was significantly associated with obesity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…17 The current study revealed that there is a statistically significant association between dyslipidemia and physical activities. Similar findings were reported from Kenya 16 and China. 25 In this study, dyslipidemia was significantly associated with obesity.…”
Section: Discussionsupporting
confidence: 90%
“…Study participants who had obese were 5.6 times more likely to be dyslipidemic compared to their underweight counterparts. A similar observation was reported from Ethiopia, 19 Kenya 16 and China. 25 Hypertension was significantly associated with dyslipidemia in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, our study indicated potential association between self-employment and elevated blood pressure in men. Although some subpopulation studies in Kenya [ 68 ], Saudi Arabia [ 69 ] and Turkey [ 70 ] reported an association between employment status and dyslipidaemia, another risk factor for CVDs, other larger studies found no significant association between occupation and dyslipidaemia [ 71 ], arguing that this association would be a result of confounding by unknown factors.…”
Section: Discussionmentioning
confidence: 99%